Victims’ relation towards the offence and victim-offender mediation - Hrnčić Jasna; Rajić Tatjana (Temida)
The paper analyse relation of victims toward the offence and their readiness for victim-offender mediation (VOM). Aims were analysis of feelings, behaviours and needs of victims regarding the offence, as well as and analysis of readiness of victims for VOM. 17 mediators assessed 41 victims and 42 offenders, participants of 41 VOM by Assessment Visit Check List (Quill, Wynne, 1993). Victims showed strong feelings of bitterness, anger and grievance more frequently than offenders, while offenders showed feeling of guilt more frequently than victims. Victims had higher defensive attitude and self-confidence then offenders. Almost all victims and offenders needed reparation and agreement with the other party. Most of them wanted to know more about the other party in conflict and were opened to contacts with him. The results were discussed in relation to current knowledge. [Projekat Ministarstva nauke Republike Srbije, br. 47011: Kriminal u Srbiji: fenomenologija, rizici i mogućnosti socijalne intervencije]